Asupan vitamin, mineral, rasio asupan kalsium dan fosfor dan hubungannya dengan kepadatan mineral tulang kalkaneus wanita - Rita Ramayulis; I Dewa Pramantara; Retno Pangastuti (Jurnal Gizi Klinik Indonesia, 2011)
Background: The prevalence of osteoporosis as defined by bone mineral density (BMD) > - 2.5 below the average of young women in Indonesia is not yet known; however the risk for the prevalence of osteoporosis is relatively high. Nutrients especially micronutrients have an important role in maintaining bone status. Yet, until today millions of people have micronutrient deficiency in vitamin and mineral such as calcium, zinc and beta-carotene.Objective: To identify the relationship between intake of vitamin A, C and mineral calcium, phosphor, zinc and ratio of intake of calcium and phosphor and BMD.Method: The study was observational with cross sectional design. Subject of the study were young women of 35 – 40 years old at Health Fitness Centre of the Ministry of Health in 2007.  There were as many as 102 subjects purposively taken. The dependent variable of the study was BMD and the independent variables were intake of vitamin A, C, and mineral calcium, phosphor, zinc and ratio of calcium and phosphor intake. The confounding variables were nutritional status, exercise, smoking, alcohol consumption, caffeine consumption, genetic, disease and medication factors. Intake data were obtained through blood record and food frequency methods. Data analysis used chi square, Fisher’s exact test and independent t-test.Results: The proportion of BMD of young women was 6,9% osteoporosis, 32,4% osteopenia and 60,8% normal. Young women with good intake of vitamin A and C, calcium, phosphor, zinc had average score of BMD as much as 0,35 point; 0,36 point and 0,97 point; 1,02 point; 1,26 point subsequently higher than those with less intake. Young women with ratio of good calcium and phosphor intake had BMD score as much as 1,13 point lower than those with ratio of poor calcium and phosphor intake. However, the relationship between intake of vitamin A, C, calcium, phosphor, zinc and ratio of calcium and phosphor intake and BMD was statistically insignificant (p>0.05).Conclusion: The relationship between intake of vitamin A, C, calcium, phosphor, zinc and ratio of calcium and phosphor intake and BMD was statistically insignifcant. Young women with good intake of vitamin A, C and calcium, phosphor, zinc tended to have higher score of BMD than those with poor intake.